How to manage risk - Bannister, Jim (London : LLP Professional publishing, 1997)
Risk management has become increasingly complex, especially with the vast sums of money at stake both in terms of assets, people and potential liabilities. This text provides a guide to a wide range of insurance subjects and their risk implications.
Includes index.
aia 05/09/16
Loans
Keywords: Risk (Insurance); Risk management; Insurance; Great Britain